PERAN STAKEHOLDER DALAM PENGEMBANGAN OBJEK WISATA AIR TERJUN KANTO LAMPO DI KELURAHAN BENG KABUPATEN GIANYAR - Darmastuti, Putu Aryadewi; Dewi, Nyoman Diah Utari; Widnyani, Ida Ayu Putu Sri (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2024)
Kanto Lampo Waterfall is located in Kelod Kangin Hamlet, Beng Village, Gianyar Regency. The development of this tourist attraction can run optimally if there is involvement from several stakeholders who have the ability. The elements that need to be involved in the development of this tourist attraction are elements in the penta helix collaboration concept consisting of elements of government, academia, society, private sector, and mass media. By maximizing the involvement of penta helix elements in the development of Kanto Lampo Waterfall attractions, the development process of this tourist attraction can run optimally. The problem faced in the development of the Kanto Lampo Waterfall tourist attraction is that there has been no involvement of private elements in the development process of the tourist attraction and there has been no continued involvement from all stakeholders involved in the development of the tourist attraction. The purpose of this study is to analyze the role of stakeholders in the development of Kanto Lampo Waterfall tourism object in Beng Village. The research method used is qualitative, with data collection techniques through observation, interviews, documentation, and literature studies. The results of this study show that four of the five elements of the helix have been involved in the development of this tourist attraction, but no involvement has been found from the private element, even though private involvement can help the marketing of this tourist attraction. Training and coaching provided by stakeholders do not have serious sustainability so the knowledge absorbed by the community does not run optimally. The use of social media by the manager of this attraction has not run optimally because of the lack of posts shared by the manager of the attraction. Keywords: Role; Stakeholders; Penta Helix; Attractions